An Evaluation on the Implementation of Management Control in Industrial Companies According to Contingency Theory - Nugraha, Adri Putra; Soewarno, Noorlailie (Universitas Brawijaya, Indonesia, 2024)
Management Control System is a tool for guiding and supervising corporate governance to ensure the achievement of organizational objectives and the effective and efficient performance of management. Industrial companies typically maintain material supplies to ensure their survival. Therefore, an appropriate control system is essential for better supervision of the raw material procurement process. This qualitative case study aims to analyze the implementation of management control in textile companies from the perspective of contingency theory. This theory posits that no single control system is universally applicable and suitable for all organizations in every situation. Most management controls implemented by companies generally align with Contingency Theory, though they have not been utilized to their full potential. Contingency theory helps companies identify the most accurate practices for corporate management control. The results showed that management control is significant for a company because the business world presents many challenges and problems from both the internal and the external environments. The results of this research enrich knowledge and thinking, expand references for further research, and provide information for researchers and company managers.